Blood glucose level during induction phase chemotherapy in childhood acute lymphoblastic leukemia - Nunki Andria; Annang Giri Moelyo; Muhammad Reza (Indonesian Pediatric Society, 2020)
Background Steroids and L-asparaginase (L-Asp) are agents used in induction phase chemotherapy for childhood acute lymphoblastic leukemia (ALL). Both agents are often reported to have the side effect of hyperglycemia, and native L-Asp is also reported to cause hypoglycemia. In ALL patients, hyperglycemic events during chemotherapy can cause lower 5-year overall and relapse-free survival. Objective To investigate the incidence of abnormal blood glucose level (BG) as the side effect of prednisone and L-Asp during induction phase chemotherapy, its predisposing factors, and its effect on remission status. Methods This cohort prospective study was conducted in 36 children aged 1-18 years who were newly diagnosed with childhood ALL at Dr. Moewardi Hospital, Surakarta, Central Java. Subjects’ nutritional status consist of wellnourished and undernourishment. Subjects underwent BG monitoring. At the end of induction phase chemotherapy, subjects underwent bone marrow puncture (BMP) evaluation to assess their response to chemotherapy and the effect of abnormal BG on remission status. Results Hypoglycemia, a combination of hypoglycemia and hyperglycemia, hyperglycemia, as well as euglycemia, were experienced by 9, 7, 6, and 14 subjects, respectively. Nutritional status was found to be a significant risk factor for abnormal BG. There was no significant difference in remission status at the end of induction phase chemotherapy between the euglycemic group and abnormal BG groups (P=0.533). Conclusion Abnormal BG during induction phase chemotherapy did not affect remission status at the end of induction phase. Undernourishment is also found to be a predisposing factor in abnormal BG.